Effecetiveness of Labour Court in Labour Dispute Management in Zimbabwe - Myambo, Admore; Munyanyi, Takawira (International Journal of Social and Administrative Sciences, 2017)
The paper focused on the effectiveness of the labour court in Zimbabwe in managing labour disputes. In assessing the effectiveness the study used a non-statistical framework which looks at three factors that can be used in determining effectiveness and these are speed, accessibility and expertise. The research was guided by Trudeau`s framework and justified by the statistics of pending cases and the cases set down for hearing and also the rate at which judgments are handed down in relation to capacities and available resources. The study highlighted that the huge backlog of cases pending at the Labour Court and the geographical locations as well as inexperienced personnel who have diminutive knowledge and expertise in labour law had a negative impact on the effectiveness of the court. Through the use of structured interviews and questionnaires the research showed that there should be prescribed qualifications and competences of the Labour Court judges to include experience in labour law and also continuous training on labour law for those already in the office. There is need to decentralize the Labour Court to every province for easy accessibility and allocate adequate resources and the Labour Court should have the powers to enforce its own decisions to be effective.